Surgical Management of Patients with Spondylodiscitis at a Tertiary Care Centre - Shrestha, Aayush; Bijukachhe, Binod; Joshi, Sachindra Raj; Dahal, Ram Krishna; Paudel, Bishal (Grande Medical Journal, 2025)
Background: Spondylodiscitis (SD) is an uncommon but potentially devastating spinal infection with increasing global incidence. Although medical therapy remains the mainstay of treatment, many patients ultimately require surgery due to neurological deficit, instability, or failure of conservative management. Method: We performed a retrospective review of 43 surgically managed SD patients between January 2019 and December 2022. Demographic data, clinical presentation, laboratory markers, microbiological findings, surgical procedures, and postoperative complications were analyzed. Pain and functional outcomes were assessed using the Visual Analog Scale (VAS) and the Oswestry Disability Index (ODI) at initial presentation and at 12 months follow-up. Result: The mean age was 47.7 years; 51.2% were female. The lumbar spine was most commonly affected (60.5%). Neurological deficits were present in 16.3% of patients. Mycobacterium tuberculosis was the predominant organism (53.5%), followed by MRSA (14%). Significant improvement was seen in VAS (8.1 → 1.1) and ODI (79.9 → 9.6) at 12 months (p < 0.001). No patient developed postoperative deformity during follow-up. Conclusion: Surgical intervention in appropriately selected patients with SD provides excellent clinical and functional outcomes. The microbiological profile in our setting underscores the high burden of tuberculosis, reinforcing the importance of region-specific diagnostic and management strategies.